Flow Experience and Organizational Citizenship Behaviour among Hotel Employees: Moderating Effect of Socio-Cultural Factor - Mark, Kasa; Zaiton, Hassan (Elsevier Ltd., 2016)
Flow, a positive psychology movement making normal life more fulfilling, is claimed to have a strong impact and proven to correlate positively with performance enhancement. As the nature of hotel jobs may give high level of stress and create many problems for people, the presence of Flow characteristics may affect among the hotel employees. The objective of this study is to distinctively investigate the influence of flow on organizational citizenship behavior (OCB) and the moderating effect of socio-cultural factors (i.e collectivism / individualism) on flow and OCB. This cross-sectional study used self-administered questionnaire, which was collected from 293 hotel employees in Sarawak, Malaysia. Confirmatory factor are analyzed using Structural Equation Modeling (SEM) via AMOS 21 and the measurement model is validated prior to testing the hypothesized model. The result reveals that Flow has a significant relationship with organizational citizenship behavior. Employees who experience Flow are likely to find their work enjoyable and intrinsically motivating. This phenomenon encourages employees to perform extra roles beyond the requirements of the formal duties. This study also revealed that there is a significant moderating effect of socio-cultural factors on the relationship between flow and organizational citizenship behavior. Specifically, individualistic employees experience Flow are more likely to display the characteristics of organizational citizenship behavior. Understanding these relationships will provide a strategy for hotel employers to retain and develop the most capable and talented human capital towards improving their competitiveness in hotel business.